IMPLEMENTATION OF SOCIAL REALITY INTERPRETATION OF THE QUR'AN SURAT ALI IMRON verse 190-191 AS A SOCIO-CULTURAL EDUCATION IN PREVENTING CORRUPTION - Nurul Musyafa’ah; Aya Mamlu’ah; Muhammad Afthon Ulin Nuha (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
In general, corruption fulfils elements such as unlawful acts, abuse of authority, and opportunities, enriching oneself, and harming the finances or economy of the State. One of the contents contained in Surah Ali Imron Verse 190-191 is dhikr praising Allah SWT with His noble names; it should be done on various occasions to always remember and connect with Allah SWT. This study uses qualitative, and this type of research is descriptive-analytic research; the purpose of this research is to determine what factors make the corrupt actions of government officials in Leran village, Senori district, and Tuban regency getting more minor and almost non-existent and how to implement the interpretation of the social reality of the Qur'an. Surah Ali Imron verses 190-191 as a socio-cultural education in preventing corrupt actions in all levels of government officials in the Leran village, Senori district, Tuban regency. In addition to interviews, data collection also uses documentation and observations with government officials in Leran village, Senori district, and Tuban regency. The results of the research on the Implementation of the Interpretation of Social Reality of the Al-Qur'an Surah Ali Imron Verse 190-191 as a Socio-Cultural Education to Prevent Corrupt Actions in Leran village, Senori district, Tuban regency, namely istighotsah together once a week this is often carried out by the Tuban regency government by instructing, involving and inviting all villages in the Tuban area including the ranks of government officials from Leran village, Senori district, Tuban regency. Another activity that is also running is reciting the Qur'an together at the Leran Village Hall every three months on Kliwon Fridays from 07.00 to 11.00. This is a separate encouragement for the ranks of government officials in the Leran village, Senori district, Tuban regency, because, in this activity, the village officials also participate in reading the Qur'an, besides some listening to the reading of the Qur'an.